Tribalism and perceived auditor independence: a research opportunity in the Arab world - Baabbad, Mohammed Abobaker; Abidin, Shamharir (Medwell Journals, 2015)
This study discusses a phenomenon prevalent in the Arab culture namely tribalism and its possible effect on auditor independence.It provides insight into collective societies, specifically tribal ones where the individual takes care of his group’s interests in what is considered as permanent loyalty to the group, often attributed to a collectivistic society. Owing to its widespread existence, it may threaten auditor’s independence, especially when both auditor and client come from one tribe or two affiliated tribes.